Economic Order Model (Q,R): Constant Lead Times And Exponential Backorder Costs - Mr. Ayinde, Oladunni Moses Dr. Gabriel K, Dr. Martin Osawaru Omorodion, (International Journal of Scientific Research and Management (IJSRM), 2014)
The paper considers the simple model of inventory models (Q,R) The backorder cost Cβ/t) is taken as an exponential function of t, the length of time of the backorder, Cβ(t) is b t b e 2 1 . The expected backorder cost is derived by obtaining the difference between the expected backorder cost at time t+L and t+L+T. In this paper demand is assumed to follow a normal distribution.Some basic mathematics of the properties of a normal distribution is introduced to simplify the derivation of the equations. The first order derivatives of the inventory backorder costs are given.